2018
DOI: 10.3390/ijms19030890
|View full text |Cite
|
Sign up to set email alerts
|

Glycoform Modification of Secreted Recombinant Glycoproteins through Kifunensine Addition during Transient Vacuum Agroinfiltration

Abstract: Kifunensine, a potent and selective inhibitor of class I α-mannosidases, prevents α-mannosidases I from trimming mannose residues on glycoproteins, thus resulting in oligomannose-type glycans. We report for the first time that through one-time vacuum infiltration of kifunensine in plant tissue, N-linked glycosylation of a recombinant protein transiently produced in whole-plants shifted completely from complex-type to oligomannose-type. Fc-fused capillary morphogenesis protein 2 (CMG2-Fc) containing one N-glyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…The reason for the N-glycoform shift from predominantly 3211 to 4601 at site N241 in ME(+) ( Figure S1) is unclear; however, it does not imply that rrBChE gains or loses activity and/or interaction with the tetramerization domain since the N241 site remains highly glycosylated. At site N341, the abundance of the In plant-based systems, several studies have reported that glycoproteins treated with kifunensine contain predominantly Man9 structures [4,23,24] and Man7/8/9 structures [25], while Man5/6/7 was the main structure found in this study. The discrepancy between our finding and others is likely due to the mass transfer limitation of kifunensine.…”
Section: Rrbche Production and Recombinant Protein Purity In The Pressupporting
confidence: 48%
See 3 more Smart Citations
“…The reason for the N-glycoform shift from predominantly 3211 to 4601 at site N241 in ME(+) ( Figure S1) is unclear; however, it does not imply that rrBChE gains or loses activity and/or interaction with the tetramerization domain since the N241 site remains highly glycosylated. At site N341, the abundance of the In plant-based systems, several studies have reported that glycoproteins treated with kifunensine contain predominantly Man9 structures [4,23,24] and Man7/8/9 structures [25], while Man5/6/7 was the main structure found in this study. The discrepancy between our finding and others is likely due to the mass transfer limitation of kifunensine.…”
Section: Rrbche Production and Recombinant Protein Purity In The Pressupporting
confidence: 48%
“…Protein expression in plant systems has the potential to provide a safe, cost-effective, and scalable method to meet the increasing need for therapeutic protein production. Plantbased expression offers several advantages to the biopharmaceutical industry, including decreased cost of production, scalability, a lack of susceptibility to mammalian pathogens, elimination of animal or human sourced raw materials, and the ability to produce complex proteins with post-translational modifications such as N-glycosylation [1][2][3][4][5]. For many therapeutic proteins, N-glycosylation is essential for protein folding, oligomerization, quality control, enzyme activity, ligand interactions, localization, and trafficking [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Protein expression in plant systems has the potential to provide a safe, cost-effective, and scalable method to meet the increasing need for therapeutic protein production. Plant-based expression offers several advantages to the biopharmaceutical industry, including decreased cost of production, scalability, lack of susceptibility to mammalian pathogens, elimination of animal- or human-sourced raw materials, and the production of complex proteins with post-translational modifications such as N -glycosylation [ 1 , 2 , 3 , 4 , 5 ]. For many therapeutic proteins, N -glycosylation is essential for protein folding, oligomerization, quality control, enzyme activity, ligand interactions, localization, and trafficking [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%